Biomechanical Comparison of Three Treatments for Medial Malleolar Fractures - Yurul, Gokhan; Demri, Sukru; Gurger, Murat; Key, Sefa; Say, Yakup; Senel, Ahmet (Istanbul Training & Research Hospital, 2021)
Introduction: Ankle fractures arc relatively common, accounting for 10% of all fractures in the skeletal system, and are the second most common lower extremity fractures after hip fractures. Here, we conduct a biomechanical comparison of three approaches-medial malleolar plate, handy tension band, and malleolar screw-for the treatment of transverse fractures of the medial malleolus. Methods: Forty-two cow tibias, cut for human consumption and free from soft tissues, were procured from the butcher. In the medial malleoli, transverse fractures were created using a bone saw, and the bones were categorized into three equal groups: bones with fractures fixed using handy tension bands, malleolar screws, and medial malleolar plates. The samples were analyzed biomechanically using equipment prepared in the laboratory, including a test device that could apply tensile and transverse forces. The data collected were interpreted after conversion into force-displacement curves. Results: When tensile force was applied, the medial malleolar plate demonstrated the greatest resistance to 2 mm displacement force and catastrophic damage force. No difference in resistance was found between the medial malleolar plate and handy tension band methods. When a transverse force was applied, the medial malleolar plate method demonstrated the greatest resistance to 2 mm displacement force. Conclusion: The medial malleolar plate is an appropriate method for the treatment of transverse fractures of the medial malleolus, although further research is required to identify any potential disadvantages of this method.
Keywords: Medial malleolus; medial malleolar plate; handy tension band; malleolar screw